NOVEL MOLECULAR METHODS FOR DISCOVERY AND ENGINEERING OF BIOCATALYSTS FROM UNCULTURED MARINE MICROORGANISMS - Agustinus Robert Uria; Yusro Nuri Fawzya; Ekowati Chasanah (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Metagenomics is a powerful cultivation-independent approach, which can be applied to gain access to the biocatalysts from uncultured marine microorganisms. Discovery of marine biocatalysts by this approach, in general, involves four main steps. First, a metagenomic library containing a pool of biocatalyst-encoding genes is constructed from a marine environment, which can be done by various methods, including cloning of enzymatically-digested DNA, uncut DNA, and PCR-amplified products. Second, the metagenomic library is screened for the genes of interest by employing the activity assay of expression product, in situ hybridization, or Polymerase Chain Reaction (PCR). Third, the obtained target genes, both functional and phylogenetic genes, are sequenced and analysed by using bioinformatic tools in order to gain information on the functional and structural properties as well as the microbial sources of the encoded biocatalysts. Finally, the target genes are expressed in suitable microbial hosts, thereby producing the corresponding recombinant biocatalysts. All existing methods in engineering of marine biocatalysts for the performance improvement can be classified into two main strategies: (i) rational design and (ii) directed evolution. Rational design, which may include the use of resctriction enzyme(s) and splicing by overlap extension (SOE), requires information on the biocatalyst`s structural and functional properties to alter specific amino acid(s). Whereas directed evolution, including error-prone PCR technique and gene shuffling, needs no such information.